Hubungan Kepemimpinan Transaksional dengan Loyalitas Karyawan Pada PT. Sejahtera Wahana Gemilang (Chitose Internasional) - Fatimatus Zahroh; Isa Anshori (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
The purpose of this research is to explain the relationship between transactional leadership and employee loyalty at PT sejahtera wahana gemilang ( Chitose internasional) This research uses a qualitative approach, namely using a literature review or study methodology. Data collection techniques include searching for literature that discusses existing problems and collecting and analyzing data from various library sources, including books, periodicals, newspapers, magazines and other materials. The results of this research are that leadership style has a positive effect on employee performance and transactional leadership style has a significant relationship with PT employee loyalty. PT sejahtera wahana gemilang ( Chitose internasional) The results of this research imply that if the transactional leadership implemented is better, the level of employee loyalty will be higher.